774PThe prognostic value of higher absolute lymphocyte counts for patients with surgically resected non-advanced gastric cancer. (1st October 2019) - Park, S J; Kim, I-H; Lee, J; Kim, H; Shin, K
Abstract: Background: Lymphocytes are an important portion of the cell-mediated immune system, and play a significant role in immune responses to cancer. We investigated whether peripheral lymphocyte are associated with disease-free survival, gastric cancer-specific survival, and overall survival in surgically resected gastric cancer. Methods: We retrospectively evaluated stage II-III gastric cancer patients who underwent curative surgical resection to analyze correlations among absolute lymphocyte counts and prognosis. Multivariable regression models adjusted for age, performance status, cancer stage, neoadjuvant/adjuvant chemotherapy use, HER2 expression were used to evaluate associations between absolute lymphocyte count, disease-free survival, gastric cancer-specific overall survival, and overall survival. Results: A total of 338 stage II-III gastric cancer patients were diagnosed from January 2011 to December 2015. At the time of diagnosis, lymphopenic were 31 (9.1%) and no patients were neutropenic. Nearly one quarter (25.1%) were ever neutropenic (ANC <1.0 K/μL) and nearly half (52.6%) were lymphopenic (ALC <1.0 K/μL) with a mean minimum ALC value of 1.00 K/μL. On multivariable analysis, ever lymphopenia predicted higher recurrence rate [HR = 12.4; 95% CI 4.9-31.3], higher gastric cancer-specific mortality [HR = 22.7; 95% CI 6.5-79.1], and higher overall mortality [HR = 36.6; 95% CI 10.3-130.0]. Five year disease-free survival was 57% for patients who were ever lymphopenic versus 96% for those who were not. Fiver year gastric cancer specific overall survival was 65% versus 98% for ever lymphopenic and never lymphopenic patients, respectively. Conclusions: Higher peripheral lymphocyte counts predicted lower recurrence rate and better overall survival from potentially curable gastric cancer, suggesting that immune function may enhance the effectiveness of non-advanced gastric cancer treatment. Legal entity responsible for the study: The author. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.